Penerapan Pemberian Olahan Daun Lembayung dalam Produksi ASI - Firdausi, Aulia; Qomar, Umi Laelatul (Prosiding University Research Colloquium, 2019)
Background: Children having no breast-milk was increasing, from 8% in 2012 to 12% in 2017 (Indonesian Health and Demography Survey, 2017). According to Central Java Health Office in 2016 the average coverage of exclusive breastfeeding in Central Java of 0-6 month old babies during the last four months was 54.2%. It was decreasing compared to the percentage of exclusive breastfeeding in 2015 (61.6%). The failure of mothers to give exclusive breastfeeding can be affected by maternal concerns, such as inadequate milk production, being influenced by the advertisement of formula milk which is considered more practical. Many people do not know about the content of lactagogum in vigna sinensis leaves which can increase milk production of postpartum mothers. Objective: To find out the application of the provision of vigna sinensis leaves in the production of breast-milk. Method: This study is a qualitative descriptive with a case study approach. Data was collected through interview, observation, literature study and documentation. Participants were 5 postpartum mothers. Result: After 7 days consuming vigna sinensis leaves, the milk production of all participants as increasing. This is indicated by the frequency of urination, the characteristics of infant urination, frequency of disposal bowl, and characteristics, the frequency of the baby sleeping and an increase in the baby's weight averaging around 300-400 grams. Conclusion: The application of processed vigna sinensis leaves can increase milk production.